Islamic Ethical Guidance for Marketing and Digital Marketing: A Study based on 7 Ps Marketing Model - Abi Huraira Rifas; Mohamed Nazar Mohamed Nushthi (El-Qish: Journal of Islamic Economics, 2025)
The concept of Marketing has grown rapidly in traditionally and technologically. 7P model in the marketing has been rounded up the whole business world effectively and efficiently. The business world is being transformed all the business and marketing activities into the digital marketing due to advanced technology today. The modern business marketing activities gave birth to online advertisement thus an ethical attention of Shariah is to be paid on the marketing activities to ensure security both buyers and sellers. Thus, this article aims to explore analytical view on prospection of the 7P model of marketing and digital marketing in Shariah perspective. This study has been designed as library research with inductive reasoning and qualitative approach. Data have been collected from primary sources (Al-Quran and Sunnah) and secondary sources (books, articles, journals, magazines). Based on content and descriptive approach, this article employed analytical and evidence explanation with the Shariah literary perspective. The study brings an ethical perspective on 7P marketing model with the light of Shariah. Marketing strategies and activities are supported by the Islamic ethical standards view. In terms of implication, this study clearly provides the Islamic perspective that the whole community should follow the Islamic guidelines to sustain the social justice.